Evidence-based geriatric medicine : a practical clinical guide - Holroyd-Leduc, Jayna M., 1970-; Reddy, Madhuri, 1972-; Wiley InterScience (Online service) (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
The latest addition to the Evidence-Based Book series, Evidence-Based Geriatric Medicine provides non-geriatrician clinicians an overview of key topics central to the care of the older patient. This guide focuses on the management of common problems in the elderly taking into account their life situations as well as treatment of specific conditions. Leading geriatricians with expertise in evidence-based medicine utilize the best available evidence and present this information in a concise, easy-to-use, question-based format. Evidence-Based Geriatric Medicine is a unique guide to the optimum management of older patients.
Function and frailty : the cornerstones of geriatric assessment / Kenneth Rockwood and Paige K. Moorhouse -- Computer-based clinical decision support systems in the care of older patients / Marina Martin and Mary K. Goldstein -- Simplifying the pill box : drugs and aging / Sudeep S. Gill and Dallas P. Seitz -- Breathing easier : respiratory disease in the older adult / Salahaddin Mahmudi-Azer -- Breathing easier : an approach to heart failure in a patient with an aging heart / Jayna M. Holroyd-Leduc, Madhuri Reddy, and Anita Asgar -- Clarifying confusion : prevention and managing delirium / Ranjani Aiyar and Jayna M. Holroyd-Leduc -- Preserving the memories : managing dementia / Dallas P. Seitz [and others] -- Enjoying the golden years : diagnosing and treating depression / Stuart Carney and Jane Pearce -- A balancing act : preventing and treating falls / Emily Kwan and Sharon Straus -- Keeping dry : managing urinary incontinence / Cara Tannenbaum -- Keeping things moving : preventing and managing constipation / Shabbir Alibhai and Dov Gandell -- Preventing and treating pressure ulcers / Madhuri Reddy [and others] -- Elder abuse / Erik J. Lindbloom, Landon D. Hough, and Karli R. Echterling Urban -- A good death : appropriate end of life care / Cari Levy and Jean Kutner.
Includes bibliographical references and index.
Print version record.
Keywords: Geriatrics; Evidence-based medicine; Geriatrics -- methods; Aged; Aging -- physiology; Evidence-Based Medicine; Geriatric Assessment; Evidence-based medicine; Geriatrics; Electronic books; E-books.